1995
DOI: 10.1088/0268-1242/10/7/008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of excess intrinsic point defects on erbium diffusion in silicon

Abstract: We have studied the effect of the annealing atmosphere on the behaviour of Er impurity atoms introduced in Czochralski-grown Si by means of diffusion from a surface source. Silicon nitride films partially covering the sulface of test structures were used to prevent any effect of the annealing atmosphere on Er diffusion. After annealing in an inert atmosphere, the penetration depth and the concentration of electrically active Er impurity atoms were found to be larger under the uncovered silicon surface than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Thermal oxidation of Si not only causes segregation distribution at the SiO 2 /Si phase boundary but also accelerates the diffusion of a number of dopants (B, P, As). According to modern concepts [1][2][3], the oxidation-enhanced diffusion (OED) and an increase in the size of extrinsic stacking faults result from generation of self-interstitials (SI) at the moving SiO 2 /Si interface. Secondary-ion mass spectrometry (SIMS) [4,5] and the spreading resistance technique [4] demonstrated that introduction of Ge impurity by implantation [4] or by deposition of a thin SiGe layer on the Si surface [5] depresses the OED of B and P dopants.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal oxidation of Si not only causes segregation distribution at the SiO 2 /Si phase boundary but also accelerates the diffusion of a number of dopants (B, P, As). According to modern concepts [1][2][3], the oxidation-enhanced diffusion (OED) and an increase in the size of extrinsic stacking faults result from generation of self-interstitials (SI) at the moving SiO 2 /Si interface. Secondary-ion mass spectrometry (SIMS) [4,5] and the spreading resistance technique [4] demonstrated that introduction of Ge impurity by implantation [4] or by deposition of a thin SiGe layer on the Si surface [5] depresses the OED of B and P dopants.…”
Section: Introductionmentioning
confidence: 99%
“…According to modern concepts [1][2][3], the oxidation-enhanced diffusion (OED) and an increase in the size of extrinsic stacking faults result from generation of self-interstitials (SI) at the moving SiO 2 /Si interface. Secondary-ion mass spectrometry (SIMS) [4,5] and the spreading resistance technique [4] demonstrated that introduction of Ge impurity by implantation [4] or by deposition of a thin SiGe layer on the Si surface [5] depresses the OED of B and P dopants.…”
Section: Introductionmentioning
confidence: 99%